2022
DOI: 10.2196/37894
|View full text |Cite
|
Sign up to set email alerts
|

Defining Recommendations to Guide User Interface Design: Multimethod Approach

Abstract: Background For the development of digital solutions, different aspects of user interface design must be taken into consideration. Different technologies, interaction paradigms, user characteristics and needs, and interface design components are some of the aspects that designers and developers should pay attention to when designing a solution. Many user interface design recommendations for different digital solutions and user profiles are found in the literature, but these recommendations have nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This research was able be an answer to the constraints of previous studies, such as research by Samrgandi [7], research by Diehl et al [8], research by Keselj et al [9], research by Pradana et al [10], research by Veza [11], research by Heriyandi et al [12], research by Jomsri [13], and research by Ahmad et al [14], which in principle has not shown a complete user interface design both in terms of appearance design and functionality. This study had similarities with several other studies, they were research by Suratno and Shafira [40], research by Che-Embi [41], research by Wheler et al [42], research by Jitnupong and Jirachiefpattana [43], and research by Jung and Yim [44], concerning the use of user interface design to show the initial physical design from an application being developed.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This research was able be an answer to the constraints of previous studies, such as research by Samrgandi [7], research by Diehl et al [8], research by Keselj et al [9], research by Pradana et al [10], research by Veza [11], research by Heriyandi et al [12], research by Jomsri [13], and research by Ahmad et al [14], which in principle has not shown a complete user interface design both in terms of appearance design and functionality. This study had similarities with several other studies, they were research by Suratno and Shafira [40], research by Che-Embi [41], research by Wheler et al [42], research by Jitnupong and Jirachiefpattana [43], and research by Jung and Yim [44], concerning the use of user interface design to show the initial physical design from an application being developed.…”
Section: Discussionmentioning
confidence: 78%
“…However, Samrgandi's [7] study limitation is that it has not yet provided a detailed explanation of the function of each feature in the user interface design. Research by Diehl et al [8] showed recommendations from an existing user interface design. They proposed a series of practical chit become a basis for various technologies development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a better interface for customer interface, it is advisable that developers and researchers explore and research about the target customers in other to develop a more UI for users. According to Diehl et al [20], UI involves the proper designing and building of any system and/or software which provides users with easy usage and navigation. The author also went further to provide steps such as discussing with UI design experts, getting and analyzing the data obtained from experts, going through the experts suggestions again and making a shorter list from the experts suggestion, and finally selecting the best-fit list of actions to be taken [20].…”
Section: User Interface Designmentioning
confidence: 99%
“…According to Diehl et al [20], UI involves the proper designing and building of any system and/or software which provides users with easy usage and navigation. The author also went further to provide steps such as discussing with UI design experts, getting and analyzing the data obtained from experts, going through the experts suggestions again and making a shorter list from the experts suggestion, and finally selecting the best-fit list of actions to be taken [20]. Because of how important the UI is in any system, other researchers have also carried various study in other to provide a better understanding of the term UI.…”
Section: User Interface Designmentioning
confidence: 99%